Analysis of User Responses to the Application of Web-Based Assessment on Character Assessment - Tanti, Tanti; Darmaji, Darmaji; Astalini, Astalini; Kurniawan, Dwi Agus; Iqbal, Muhammad (Journal of Education Technology, 2021)
There are currently several obstacles in the assessment using conventional media, including excessive use of paper, which causes environmental damage, and increases in school fees to conduct an assessment. In addition, it is less effective in conducting assessments because it takes a long time to assess the results of student answers manually. . Conventional media allows fraud and results in a lack of confidence in the assessment results. This study aims to analyze user responses using web-based assessment as a character assessment medium. The population of this study amounted to 91 students. This study uses a mixed-method explanatory method with descriptive analysis and qualitative methods. The results of the study show that the user response obtained an average value of 3.52, which includes the SB category (excellent) because the use of the website can save time, display real-time data, and is very easy to use anywhere, so with a good response from users make this web-based assessment suitable for use in student character assessment. This research implies that teachers can use web-based assessment in conducting assessments.